Effect of fungi and N-fixing bacteria on the solid state fermentation of rice straw - RANE, SHARMILA; PUNIYA, A K; SINGH, KISHAN (The Indian Journal of Animal Sciences, 2014)
SSF of rice straw was carried out for 7 days at 65% inoisture content, with and without Phanerochaete chrysosporium, P. ostreatus and Coprinus fimetarius (3 and 5%) in combination of Azospirllum brasilense and Azotobacter chrooococcum (3 and 5%having 10 8- 109 cells/ml). After the fermentation period, the SSF were evaluated for different parameters. Rice straw had initial pH, CP content, DM and digestibility o f5.30, 3.80, 91.20 and 35.00% respectively. The values for different parameters changed with P. Chrysosporium, P. ostreatus and C. finetarius along with asymbiotic nitrogen-fixers (A. brasilense and A. chroocooccum). Maximum DML. (4.59%) was observed in straw with P. ostreatus withA. brasilense. The digestibility and CP content of straw after inoculation with P. ostreatus and A. brasilense was in range of 49.57 to 50.00 and 4.82 to 5.88% respectively. The lowering of the ADL value from an initial value of 6.64 to 6.30% in straw affected the biodegradation process-taking place during the SSF. Thc highest PE observed in straw (2.18%) was due to the synergistic growth of P. astreatus and A. brasilense during the SSF.